Systemic and mucosal immune reactivity upon Mycobacterium avium ssp. paratuberculosis infection in mice - Koc, Arzu; Bargen, Imke; Suwandi, Abdulhadi; Roderfeld, Martin; Tschuschner, Annette; Rath, Timo; Gerlach, Gerald F.; Hornef, Mathias; Goethe, Ralph; Weiss, Siegfried; Roeb, Elke; Justus Liebig University Giessen (My University, 2014)
Mycobacterium avium ssp. paratuberculosis (MAP) is the cause of Johne´s disease, an inflammatory bowel disorder of ruminants. Due to the similar pathology, MAP was also suggested to cause Crohn´s disease (CD). Despite of intensive research, this question is still not settled, possibly due to the lack of versatile mouse models. The aim of this study was to identify basic immunologic mechanisms in response to MAP infection. Immune compromised C57BL/6 Rag2-/- mice were infected with MAP intraperitoneally. Such chronically infected mice were then reconstituted with CD4+ and CD8+ T cells 28 days after infection. A systemic inflammatory response, detected as enlargement of the spleen and granuloma formation in the liver, was observed in mice infected and reconstituted with CD4+ T cells. Whereby inflammation in infected and CD4+CD45RBhi T cell reconstituted animals was always higher than in the other groups. Reconstitution of infected animals with CD8+ T cells did not result in any inflammatory signs. Interestingly, various markers of inflammation were strongly up-regulated in the colon of infected mice reconstituted with CD4+CD45RBlo/int T cells. We propose, the usual non-colitogenic CD4+CD45RBlo/int T cells were converted into inflammatory T cells by the interaction with MAP. However, the power of such cells might be not sufficient for a fully established inflammatory response in the colon. Nevertheless, our model system appears to mirror aspects of an inflammatory bowel disease (IBD) like CD and Johne´s diseases. Thus, it will provide an experimental platform on which further knowledge on IBD and the involvement of MAP in the induction of CD could be acquired.
Keywords: ddc:610